Planthopper-Secreted Salivary Calmodulin Acts as an Effector for Defense Responses in Rice - Fu, Jianmei; Shi, Yu; Wang, Lihua; Tian, Tian; Li, Jing; Gong, Lei; Zheng, Zhouting; Jing, Maofeng; Fang, Jichao; Ji, Rui (Frontiers in Plant Science, 2022)
The brown planthopper (Nilaparvata lugens, BPH) and small brown planthopper (Laodelphax striatellus, SBPH) are major pests of rice (Oryza sativa) in Asia. These piercing-sucking insects secrete saliva into the host during feeding. Nevertheless, it is largely unknown how planthoppers use salivary effectors to enable continuous feeding on rice. Here, we screened their salivary proteomes and selected eight salivary proteins conserved between SBPH and BPH as candidate effectors. Silencing calmodulin (CaM) impeded BPH and SBPH from penetrating the phloem. Hence, their food in-take, survival, and fecundity on rice plants were reduced. By contrast, CaM silencing had a small effect on the survival rate of BPH and SBPH raised on artificial diet. The CaM amino acid sequences were the same for both BPH and SBPH. CaM was highly expressed in their salivary glands and secreted into the rice plants during feeding. Bacterially expressed recombinant CaM protein exhibited calcium-binding activity. In planta expression disclosed that CaM was localized to the plant cytoplasms and nuclei and suppressed plant defenses such as hydrogen peroxide (H2O2) accumulation and callose deposition. CaM-silenced BPH and SBPH nymphs elicited relatively high lev-els of H2O2 and callose accumulation in rice plants. The foregoing results reveal that CaM is an effector as it enables the planthopper to reach the phloem by suppressing callose deposition and H2O2 accumulation in rice.